Echoes of the fragmentary tragedy of Sophocles and Euripides: Laocoon, Sinon, Phrygians and Philoctetes in the Aeneid (2, 1-227) (Argos, 2022)
In this work we will analyze some aspects of the fragmentary tragedy of Sophocles (Laocoon, Sinon, Phrygians) and Euripides (Philoctetes), appropriated by Virgil for the narration of the fall of Troy (specifically, A. 2, 1-227). Our objective is to identify and examine various intertextual elements that constitute the passages starring Laocoon and Sinon. We will try to demonstrate, on the one hand, that the episode of the priest suggests some possible answers to questions about Sophocles’ Laocoon; on the other, Virgil’s intense attachment to the fragmentary material of both tragedians to configure the character of the Greek trickster, Sinon.
Keywords: Virgil; Sophocles; Euripides; Fragmentary tragedy; Intertextuality